The ELIMED transport and dosimetry beamline for laser-driven ion beams - Romano, F.; Schillaci, F.; Cirrone, G.A.P.; Cuttone, G.; Scuderi, V.; Allegra, L.; Amato, A.; Amico, A.; Candiano, G.; De Luca, G.; Gallo, G.; Giordanengo, S.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2016)
A growing interest of the scientific community towards multidisciplinary applications of laser-driven beams has led to the development of several projects aiming to demonstrate the possible use of these beams for therapeutic purposes. Nevertheless, laser-accelerated particles differ from the conventional beams typically used for multiscipilinary and medical applications, due to the wide energy spread, the angular divergence and the extremely intense pulses. The peculiarities of optically accelerated beams led to develop new strategies and advanced techniques for transport, diagnostics and dosimetry of the accelerated particles. In this framework, the realization of the ELIMED (ELI-Beamlines MEDical and multidisciplinary applications) beamline, developed by INFN-LNS (Catania, Italy) and that will be installed in 2017 as a part of the ELIMAIA beamline at the ELI-Beamlines (Extreme Light Infrastructure Beamlines) facility in Prague, has the aim to investigate the feasibility of using laser-driven ion beams for multidisciplinary applications. In this contribution, an overview of the beamline along with a detailed description of the main transport elements as well as the detectors composing the final section of the beamline will be presented.